Pulmonary Tuberculosis Incidence Rate with Genexpert Examination Method at Mlati II Public Health Center, Sleman In 2020-2023 - Nila Wati; Isnin Aulia Ulfah Mu’awanah; Arifiani Agustin Amalia (Universitas Muhammadiyah Palu, 2024)
Tuberculosis cases in adults in the Special Region of Yogyakarta are still quite high. In 2019, data wasobtained that the number of Tuberculosis cases in the Special Region of Yogyakarta in adults was 2,974cases. The results of the GeneXpert examination showed that the most positive cases of Tuberculosis werefound in Yogyakarta City, reaching 1,946 people, then followed by Sleman Regency 1,604 cases, YogyakartaCity 986 cases, Bantul Regency 643 cases, Kulonprogo Regency 177 cases, Gunugkidul Regency 422 cases,Sleman Regency 746 cases. The purpose of this study was to determine the incidence of pulmonaryTuberculosis using the Genexpert examination method at the Mlati II Health Center in 2020-2023. Thistype of research is a descriptive analytical study with a cross-sectional approach using secondary data atthe Mlati II Sleman Health Center in 2020-2023. Based on the results of the study, the incidence ofpulmonary tuberculosis was obtained using the Genexpert examination method at the Mlati II SlemanHealth Center in 2020 to 2023 from 587 pulmonary tuberculosis patients, 89 patients were positive and498 patients were negative. Meanwhile, of the 89 positive patients, 52 were male positive patients and 37were female positive patients. Based on the characteristics of patients with pulmonary tuberculosis at theMlati II Sleman Health Center, totaling 89 people, including 4 patients aged 1-5 years, 4 patients aged 6-11years, 20 patients aged 12-25 years, 27 patients aged 26-45 years, 27 patients aged 46-65 years and 7patients aged >65 years. The results of the study showed that the lowest number of patients diagnosedwith tuberculosis was in 2021 with 17 positive patients and 40 negative patients. The Genexpertexamination in 2020 was 18 positive patients (24%). In addition, The results of the study showed that thepercentage of tuberculosis cases from 2020 to 2023 decreased, but the number of cases increased, this wasdue to the increasing population of suspected tuberculosis in 2022 and 2023. The number of suspectedtuberculosis patients in 2020 was 75 cases and in 2021 decreased by 57 cases. The increase occurred in2022 with the number of suspected tuberculosis cases of 200 and in 2023 there were 255 cases.Keywords: Genexpert test, suspect tuberculosis, Suspected TB, Tuberculosis, Molecular Rapid Test,Micobacter